MONETIZING RELATIONSHIPS: STREAMING ALONE WITH ALL OF YOUR FRIENDS - Skardzius, Karen (AoIR Selected Papers of Internet Research, 2020)
This paper is derived from a larger project that examines the experiences of women who live-stream video games on the Twitch.tv platform. To date, much of the research that has been done in the area of streaming is concerned with streamers who have a large following and/or derive their main source of income from streaming. Rather than directing more attention to those streamers who have attained ‘success’ as Twitch would frame it, this study is centered around a group of streamers unique from those who are typically the focus. First, I discuss the ways monetization influences community building. Second, I discuss some of the implications of paying for attention. Third, I discuss the pressure streamers feel to perform a particular kind of authenticity around monetization. Finally, I will discuss how monetization creates friction and competition between streamers. This work contributes the perspectives of 5 women whose experiences have been largely overlooked by existing research about streaming, as well as the analysis of another 50 Twitch channels run by women from diverse backgrounds and streaming interests. These findings demonstrate that the monetization features available to streamers and the everyday practices that have emerged through Twitch centered around monetization have a lot of influence over how people relate to each other, even for those streamers who are not trying to monetize their channels.